The Incremental Information Content of Accrual versus Cash Flows - Bowen, Robert M.; Burgstahler, David; Daley, Lane A. (The Accounting Review, 1987)
[Current financial reporting practices have traditionally emphasized measures of accrual earnings. On the other hand, the link between future cash flows and firm value is well accepted by financial economists, and recently there has been increased interest in measures of cash flow. This paper provides evidence on the role of accrual (i.e., earnings and working capital from operations [WCFO]) and cash flow measures in an explanatory model of security prices. This issue is first examined by testing for an association between unexpected security returns and unexpected cash flows, after controlling for the relation between unexpected returns and unexpected earnings. We also examine the obverse issue by testing for an association between unexpected security returns and unexpected earnings, after controlling for the relation between unexpected returns and unexpected cash flows. We test these relations in two contexts: in results pooled over the entire ten-year time period studied and in year-by-year cross-sectional regressions. Results for our complete sample are generally consistent with: (1) cash flow data having incremental information content relative to that contained in earnings; (2) cash flow data having incremental information content in addition to that contained in earnings and WCFO; and (3) accrual data (i.e., earnings and WCFO) jointly and separately having incremental information content in addition to that contained in cash flow data. However, the results do not support the hypothesis that WCFO has incremental information content relative to that contained in earnings.]